2020
DOI: 10.1111/jfb.14326
|View full text |Cite
|
Sign up to set email alerts
|

Species‐specific schooling behaviour of fish in the freshwater pelagic habitat: an observational study

Abstract: Social living of animals is a broadly occurring phenomenon, although poorly studied in freshwater systems, fish schooling behaviour is an excellent example. The composition of fish schools, species-specific schooling tendencies and preferences of adult fish were studied in the pelagic habitat of the Římov Reservoir, Czech Republic. Video recordings captured over a total of 34 days (16 h per day) in the clear water period of three seasons were analysed. From four species identified as schoolforming speciesbream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…The shoaling behavior of fish during the day was captured by both hydroacoustics and trawling, and revealed another clear spatio‐temporal pattern (Holubová et al, 2020). Shoals were regularly observed by hydroacoustics and while different tows were unbalanced (in one too many fish, the next one practically empty), they were also evident in trawl catches (if the trawl hit the shoal, the catch was high, if not the trawl was empty).…”
Section: Discussionmentioning
confidence: 99%
“…The shoaling behavior of fish during the day was captured by both hydroacoustics and trawling, and revealed another clear spatio‐temporal pattern (Holubová et al, 2020). Shoals were regularly observed by hydroacoustics and while different tows were unbalanced (in one too many fish, the next one practically empty), they were also evident in trawl catches (if the trawl hit the shoal, the catch was high, if not the trawl was empty).…”
Section: Discussionmentioning
confidence: 99%
“…Categorised as a 'compulsory schooling' species (Karst 1968) and an 'obligate schooler' (Haberlehner 1988), A. alburnus occurs almost exclusively in shoals, which commonly consist of 30-50 individuals (Holubová et al 2020) and move through the surface layer of the water column, usually at a depth not exceeding 1.5 m (Vašek et al 2009). Underwater observations demonstrated that adult A. alburnus shoals move rapidly (Karst 1968), positioned near the water's surface (Karst 1968;Vinyoles et al 2008), and that high swimming speeds preclude other species (e.g.…”
Section: Activities and Social Patternsmentioning
confidence: 99%
“…The tracks for the evaluation dataset were selected at an ecologically relevant period of 30 min. We selected 30 min as it provides su cient nescale movement data from piped weirs for ecological research and management actions [73,74]. The training dataset had temporal buffers of 1, 5, 10, 15, 20, 30, 45 and 60 min.…”
Section: Cross-validation Routinementioning
confidence: 99%